Extending the theory of planned behavior to understand hotel managers pro-enviromental behavior in supply procurement process - Ramli, Mohammad Ammalluddin (Logistics, supply chain, sustainability and global challenges, 2025)
Hotel managers' behaviour and decision making significantly impacts hotel energy consumption, operating costs, and environmental issues. Encouraging pro-environmental behaviours among hotel managers is vital for sustainable development in the hotel and tourism sector. This study aims to understand the factors that drive hotel managers to adopt sustainable practices, especially in supply chain management, to combat global warming. An expanded model based on the Theory of Planned Behavior was developed, incorporating elements like global warming consciousness, actions to alleviate global warming, emotional responses, and varying supply expenses. An online survey was conducted with 479 hotel managers involved in the supply chain procurement process. Data analysis utilized partial least squares-structural equation modelling techniques, revealing that global warming consciousness greatly influences managers' attitudes and purposes to engage in sustainable practices. Fostering actions to reduce global warming also positively impacts these purposes. Additionally, anticipated emotions such as remorse are critical in shaping behavioural purposes. Findings also indicate that personal attitudes, subjective social standards, and perceived selfcontrol over sustainability efforts influence managers' purposes in practising sustainable resourcing. Notably, varying food and beverage supply expenditure levels moderate seven out of nine of the proposed hypotheses. This research identifies a substantial gap in the current literature regarding the relationship between hotel managers' sustainable practices and global warming within the hotel and tourism sector. By employing an extended Theory of Planned Behavior framework, this research makes a meaningful contribution to the ongoing effort to improve sustainability in the hotel and tourism sector, particularly in Malaysia.
Keywords: extendend theory of planned behaviour; hotel and tourism sector; hotel manager behaviour; hotelski in turistični sektor; Malaysia; Malezija; okolju prijazno ravnanje; pro-environmental behaviour; ravnanje hotelskih menedžerjev; razširjena teorija načrtovanega ravnanja